Evaluation of nutritive value and shelf life of strawberry genotypes - Chowhan, Sushan; Roni, Md Shyduzzaman; Ahmed, Shaikh Shakib; Uddin, Hanif; Hasan, Md Mahmudul (Asian Journal of Medical and Biological Research, 2016)
An investigation was carried out to evaluate the nutritive value and shelf life of five strawberry genotypes. It was found that under fresh condition the highest ascorbic acid (45.76 mg/100g) was obtained by Rabi-3 and the highest ?-carotene (15.09 IU/100g) by Festival. The maximum amount of reducing sugar (6.373 g/100g) and non-reducing sugar (2.947 g/100g) was recorded in Camarosa and Festival respectively. The maximum amount of calcium (0.480%) in BADC Strawberry, iron (93.50 ppm) in Rabi-3, phosphorus (0.081%) and potassium (0.854%) in BARI Strawberry-1 was recorded. Under different temperature and packaging conditions, polyethylene package at 40C proved to be superior to others in all respects. The highest shelf life (47.00 days) and ascorbic acid (42.76 mg/100g) after four days of storage was obtained by Camarosa in this condition; whereas the lowest shelf life (2.33 days) and ascorbic acid (10.12 mg/100g) was recorded in BADC Strawberry in plastic punnet package at 250C. Asian J. Med. Biol. Res. March 2016, 2(1): 19-26